Implementasi Pembelajaran Bernalar Kritis Dalam Pendidikan Agama Islam Dan Budi Pekerti Dengan Integrasi ICT Di SMPN 1 Salatiga - Guntur Wicaksono; Alfi Rohmatul Azizah; Dhewy Laily Choirrushsholih Cholisha; Win Listyaningrum Arifin (Edification Journal : Pendidikan Agama Islam, 2026)
This study focuses on describing the implementation of deep learning integrated with Information and Communication Technology (ICT) in the subject of Islamic Religious Education and Character Building (PAI and BP) at SMP Negeri 1 Salatiga. Deep learning plays a crucial role in shaping students’ critical, reflective, and meaningful thinking patterns, particularly in the digital era characterized by an abundance of information. This research employs a descriptive qualitative method with data collection techniques consisting of observation, in-depth interviews, and documentation. The research subjects include PAI and Character Building teachers, eighth-grade students, the vice principal for curriculum affairs, and the principal. Data analysis follows the interactive model of , which includes the stages of data condensation, data display and conclusion drawing. data validity is ensured through source and method triangulation. The findings indicate that teachers have implemented deep learning through activities such as analyzing religious case studies, conducting reflective projects, and utilizing digital media such as Google, YouTube, and Quizizz. The integration of ICT has encouraged students to think critically, enhanced active participation, and strengthened the internalization of Islamic values. Moreover, the school environment’s excellence in the MAPSI CCI field has contributed to the success of this learning process. Therefore, ICT-based deep learning is considered effective in fostering students’ religious character and higher-order thinking skills.